Fermi level shift in carbon nanotubes by dye confinement. (August 2019) - Almadori, Y.; Delport, G.; Chambard, R.; Orcin-Chaix, L.; Selvati, A.C.; Izard, N.; Belhboub, A.; Aznar, R.; Jousselme, B.; Campidelli, S.; Hermet, P.; Le Parc, R.; et al.
Abstract: Dye confinement into carbon nanotube significantly affects the electronic charge density distribution of the final hybrid system. Using the electron-phonon coupling sensitivity of the Raman G-band, we quantify experimentally how charge transfer from thiophene oligomers to single walled carbon nanotube is modulated by the diameter of the nano-container and its metallic or semiconducting character. This charge transfer is shown to restore the electron-phonon coupling into defected metallic nanotubes. For sub-nanometer diameter tube, an electron transfer optically activated is observed when the excitation energy matches the HOMO-LUMO transition of the confined oligothiophene. This electron doping accounts for an important enhancement of the photoluminescence intensity up to a factor of nearly six for optimal confinement configuration. This electron transfer shifts the Fermi level, acting on the photoluminescence efficiency. Therefore, thiophene oligomer encapsulation allows modulating the electronic structure and then the optical properties of the hybrid system. Graphical abstract: Image 1